Sini Decoction Ameliorates Colorectal Cancer and Modulates the Composition of Gut Microbiota in Mice - Wang, Yishan; Zhang, Xiaodi; Li, Jiawei; Zhang, Ying; Guo, Yingjie; Chang, Qing; Chen, Li; Wang, Yiwei; Wang, Siyao; Song, Yu; Zhao, Yongkun; Wang, Zhihong (Frontiers in Pharmacology, 2021)
Sini Decoction (SND), as a classic prescription of Traditional Chinese Medicine (TCM), has been proved to be clinically useful in cardiomyopathy and inflammatory bowel diseases. However, the role and mechanism of SND in colitis-associated cancer remains unclear. This study aims to evaluate the effect of SND on colorectal cancer(CRC) symptoms and further explore the changes of gut microbes mediated by SND extract in azoxymethane (AOM)/dextran sulfate sodium (DSS)-induced CRC mice through 16S rRNA sequencing. Our results indicated that treatment with SND extract could ameliorate the tumors' malignant degree by decreasing tumor number and size. Also, the expression levels of Cyclooxygenase 2 and Mucin-2, which are typical CRC biomarkers, were reduced compared to the CRC group. In the meantime, SND extract can upregulate CD8+ T lymphocytes' expression and Occludin in the colonic mucosal layer. Besides, SND inhibited the expression of CD4+ T cells and inflammatory cytokines in CRC tissue. According to bioinformatics analysis, SND extract was also suggested could modulate the gut microbial community. After the SND treatment, compared with the CRC mice model, the number of pathogenic bacteria showed a significant reduction, including Bacteroides fragilis and Sulphate-reducing bacteria; and SND increased the relative contents of the beneficial bacteria, including Lactobacillus, Bacillus coagulans, Akkermansia muciniphila, and Bifidobacterium. In summary, SND can effectively intervene in colorectal cancer development by regulating intestinal immunity, protecting the colon mucosal barrier, and changing the intestinal microbiota composition in mice.